The Role of IL-17 and Related Cytokines in Inflammatory Autoimmune Diseases - Taku Kuwabara; Fumio Ishikawa; Motonari Kondo; Terutaka Kakiuchi (Hindawi Limited, 2017)
Interleukin-17 (IL-17) induces the production of granulocyte colony-stimulating factor (G-CSF) and chemokines such as CXCL1 and CXCL2 and is a cytokine that acts as an inflammation mediator. During infection, IL-17 is needed to eliminate extracellular bacteria and fungi, by inducing antimicrobial peptides such as defensin. This cytokine also plays an important role in chronic inflammation that occurs during the pathogenesis of autoimmune diseases and allergies such as human rheumatoid arthritis (RA) for which a mouse model of collagen-induced arthritis (CIA) is available. In autoimmune diseases such as RA and multiple sclerosis (MS), IL-17 is produced by helper T (Th) cells that are stimulated by IL-1β and IL-6 derived from phagocytes such as macrophages and from tissue cells. IL-17 contributes to various lesions that are produced by Th17 cells, one subset of helper T cells, and by γδ T cells and innate lymphoid cells. It strongly contributes to autoimmune diseases that are accompanied by chronic inflammation. Thus, a functional understanding of Th17 cells is extremely important. In this review, we highlight the roles of cytokines that promote the development and maintenance of pathogenic Th17 cells in autoimmune diseases.